Exploratory Item Factor Analysis: A practical guide revised and up-dated. - Lloret-Segura, Susana; Ferreres-Traver, Adoración; Hernández-Baeza, Ana; Tomás-Marco, Inés (Anales de Psicología / Annals of Psychology, 2014)
Exploratory Factor analysis is one of the techniques used in the development, validation and adaptation of psychological measurement instruments. Its use spread during the 1960s and has been growing exponentially thanks to the advancement of information technology. The criteria used, of course, have also evolved. But the applied researchers, who use this technique as a routine, remain often ignorant of all this. In the last few decades numerous studies have denounced this situation. There is an urgent need to update the classic criteria. The incorporation of the most suitable criteria will improve the quality of our research. In this work we review the classic criteria and, depending on the case, we also propose current criteria to replace or complement the former. Our objective is to offer the interested applied researcher updated guidance on how to perform an Exploratory Item Factor Analysis, according to the “post-Little Jiffy” psychometrics. This review and the guide with the corresponding recommendations have been articulated in four large blocks: 1) the data type and the matrix of association, 2) the method of factor estimation, 3) the number of factors to be retained, and 4) the method of rotation and allocation of items. An abridged version of the complete guide is provided at the end of the article.